2021
DOI: 10.1111/ics.12745
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid 2‐glucoside: An ascorbic acid pro‐drug with longer‐term antioxidant efficacy in skin

Abstract: Objective Deleterious effects of pollutants and ultraviolet radiation on the skin can be attenuated using formulations containing antioxidants. However, these have disadvantages, including chemical instability, photodegradation, poor bioavailability or biological activity. Here, two commercial formulations were evaluated: one optimized to stabilize and deliver ascorbic acid (AA) at 15% and the other containing a glucoside form of AA, namely ascorbic acid 2‐glucoside (AA2G), at 1.8% and at a physiological pH. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
(73 reference statements)
2
5
0
1
Order By: Relevance
“…The significant decrease in vitamin C stability was observed after incubation at 37°C for 20 min followed by a pH adjust to 9.0 immediately before HPLC injection. This is consistent with other reports showing that vitamin C is only stable in acidic formulations with pH below 3.5 [8].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The significant decrease in vitamin C stability was observed after incubation at 37°C for 20 min followed by a pH adjust to 9.0 immediately before HPLC injection. This is consistent with other reports showing that vitamin C is only stable in acidic formulations with pH below 3.5 [8].…”
Section: Resultssupporting
confidence: 94%
“…The s factor is related to the possible conversion of AA2G to vitamin C, and subsequent degradation of vitamin C, as AA2G diffuses through the skin sample. A recent study using viable human skin explants showed that AA2G is completely metabolized to vitamin C during passive diffusion through 450 μm thick skin [8]. This is consistent with our results of passive diffusion shown in Figure 6a, although under our experimental conditions vitamin C is not stable and was not quantified.…”
Section: In Vitro Dermal Delivery Of Ascorbic Acid 2-glucosidesupporting
confidence: 92%
See 1 more Smart Citation
“…Because this compound has strong hydrophilicity, its skin permeability is lower than that of AA [ 93 ]. This compound is relatively stable in the cosmetic formulation and, when topically applied, it can be enzymatically hydrolyzed in the skin, producing AA [ 93 , 94 ].…”
Section: Various Approaches To Maximize the Efficacy Of Aamentioning
confidence: 99%
“…In summary, certain hydrophobic AA precursors could be more effective than AA itself in increasing the concentration of AA in the cytoplasm because it is easy to pass through the cell membrane [ 83 , 88 ]. Topically applied AA glycosides can serve as a reservoir for AA because they continuously release AA by enzymatic hydrolysis in the skin [ 94 ]. Multifunctional hybrid compounds developed by covalently combining two substances with different biological activities and physicochemical properties would have added benefits [ 84 , 87 ].…”
Section: Various Approaches To Maximize the Efficacy Of Aamentioning
confidence: 99%